EFEKTIFITAS MEDIASI DALAM PERKARA PEMBAGIAN HARTA BERSAMA AKIBAT PERCERAIAN DI PENGADILAN AGAMA PALU KELAS I A - Moh Nafri; Moh Didi Permana (Fakultas Hukum Universitas Muhammadiyah Palu, 2019)
The peace efforts referred to in Article 130 paragraph (1) of the HIR are imperative. This means that the judge is obliged to reconcile the parties to the dispute before the trial process begins. The judge tried to reconcile with good methods so that there was a meeting point so that there was no need for a long and tiring trial process. Nevertheless, the peace efforts carried out still prioritize the interests of all parties to the dispute so that all feel satisfied and no one feels disadvantaged. In the life of a family or household in addition to issues of rights and obligations as husband and wife, then the problem of property can also be a base that is the cause of various disputes or tensions in marital life, because property is the material basis of family life . The purpose of this study was to determine the effectiveness of mediation in cases of sharing of shared assets resulting from divorce in the Palu I Class A Religious Court and to find out the obstacles in the implementation of mediation in the case of sharing of shared assets in the Class I A Religious Court of Palu. The research method used is empirical research. The use of this type of research is based on the formulation of the problem raised as a logical consequence of the legal issue of research in the background of the problem. Summary of research results are general factors that cause ineffectiveness of mediation in the case of sharing of assets in the Religious Courts are firstly the level of community compliance that undergoes a very low mediation process, this factor which is the main cause of ineffective mediation in the Religious Courts. Secondly, the obstacles in the implementation of mediation in the case of sharing of shared assets is because in addition to the head of the Religious Court, judges appointed as mediators have not all participated in mediation training conducted by the Supreme Court of the Republic of Indonesia. Keywords: Mediation, Joint Assets, Divorce